Pelatihan Entrepreneurship dan Strategi Pemasaran Pada Pelaku UMKM di Kota Mataram dan Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Mataram - Abdurrahman; Adrianda Anwar; Nila Rahayu; Zamroni Alpian Muhtarom; I.G.A. Arista Pradnyani (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Abstract: The purpose of this training is to increase the understanding of MSMEs in the city of Mataram and business actors from FEB Unram students through entrepreneurship training and sustainable marketing strategies. In addition, this training is conducted to provide added value and increase various knowledge about the entrepreneurial spirit and marketing strategies that help sustainability their business. The method of implementing this service program is carried out with initial assistance to partners related to the problems and constraints faced. Therefore, both parties implemented the program through three stages, namely preparation of materials, training or outreach, and recommendations.